Fungsi Pemerintah Desa Nekbaun Kecamatan Amarasi Barat Kabupaten Kupang Dalam Meningkatkan Kesejahteraan Masyarakat - Trivas Elisa Sonbai; Kotan Y Stefanus; Yohanes Tuan (Artemis Law Journal, 2026)
This study aims to analyze how the Nekbaun village governmet,Amarasi west –district,Kupang district, functions to improve the welfare of the community. This research focusse on two main questions:(1) How is the function of the Village Government regulated in improving the welfare of the Village community? and (2) How does the implementation of functions and obstacles faced by the Village government in improving the welfare of the Nekbaun Village community?This research is normative juridical legal research. Based on the results of research conducted by the author, it is known that The functions of the village government are generally divided into 3, namely the regulatory function, service function and empowerment function. the Nekbaun Village government continues to optimize the welfare of the Nekbaun village community both in terms of infrastructure and superstructure to improve neglected public services. However, in carrying out the function of improving the welfare of the community, it is inseparable from factors that hinder the process of implementing these functions. The obstacles experienced are in the form of physical obstacles, socio-cultural obstacles, education levels, and economic obstacles. This is what shows that welfare is not evenly distributed in the Nekbaun Community area. Therefore, the village government needs to pay more serious attention to the Nekbaun Village community with existing programs and the government is also expected to broadcast every program that has been implemented so that the program is run on target. In addition, about the importance of supporting and participating in implementing government programs to improve community welfare.